2022
DOI: 10.1016/j.metop.2021.100147
|View full text |Cite
|
Sign up to set email alerts
|

An immediate post op and follow up assessment of circulating adipo-cytokines after bariatric surgery in morbid obesity

Abstract: Background Bariatric surgery has emerged as a promising treatment for improving adipose tissue dysfunction in obesity, but the mechanisms for such amelioration are still not known. This study comprehensively explores a panel of adipo-cytokines in individuals with obesity undergoing bariatric surgery, in conjunction with markers of insulin resistance, at three time points i.e., pre-op, immediate post-op and 6 months post-surgery. Methods It is a case-control prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(59 reference statements)
2
3
0
Order By: Relevance
“…In line with previous study, we showed that both LSG and RYGB improve the obesity and inflammatory conditions of patients, However, a gastric bypass was found to be more beneficial as compared to gastrectomy [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous study, we showed that both LSG and RYGB improve the obesity and inflammatory conditions of patients, However, a gastric bypass was found to be more beneficial as compared to gastrectomy [ 54 ].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, there was a positive correlation between MCP-1 levels and BMI. A significant decrease in MCP-1 levels was seen with weight loss after BS, a finding in keeping with previous observations [76]. Collectively, these findings support the notion that MCP-1 plays an important role in asthma and obesity pathogenesis.…”
Section: 2supporting
confidence: 91%
“…To confirm the close association of obesity with inflammation, it is well known that obese subjects almost always show moderately elevated plasma levels of inflammatory markers such as CRP and IL-6 [25]. Furthermore, the loss of fat mass, induced by lifestyle modifications, pharmacological therapy and/or bariatric surgical treatment, determines a reduction in inflammatory cytokine levels and an improvement in the inflammatory state that characterizes obesity, confirming the primary role of adipose tissue in the pathogenesis of this condition [26].…”
Section: Discussionmentioning
confidence: 99%